A policy framework to facilitate integrated Forest Landscape Restoration (FLR) to enhance local livelihoods in Indonesia - Adiwinata, A.; Wicaksono, S.A.; Ichsan, A.C.; Yumn, A.; Goib, B.K.; Muslimah, S.; Susanti, F.N.; Purwanto, E. (CIFOR-ICRAF, 2022)
In Indonesia, an integrated Forest Landscape Restoration (FLR) approach has been proposed as one of the solutions to address degraded lands, including 14 million ha of critical and very critical lands (Ministry of Environment and Forestry (2019). However, the land use competition has been quite high and intensive, particularly between sectors. This situation has provided serious challenges for the implementation of FLR on the ground. In the absence of integrated policy and regulatory frameworks for the landscape approach and FLR at the national level, various organizations have initiated a range of programmes and strategic approaches in moving forward to implement these approaches. Per our review, there are opportunities and challenges for the application of a landscape-based approach, FLR and a combination of the two.